2022
DOI: 10.1021/acs.jafc.2c06418
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Key Flavor Compound 2,3,5-Trimethylpyrazine in Human Urine

Abstract: Pyrazines are among the most important compound class conveying the odor impressions “roasty”, “nutty”, and “earthy”. They are formed by the Maillard reaction and occur ubiquitously in heated foods. The excretion of metabolites of the key flavor odorant 2,3,5-trimethylpyrazine, abundant in the volatile fraction of roasted coffee, was investigated. Based on literature suggestions, putative phase 1 and phase 2 metabolites were synthesized, characterized by nuclear magnetic resonance and mass spectroscopy data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
2
2
Order By: Relevance
“…Among them, strain LC-6 (B. amyloliquefaciens) had a relatively higher TMP yield of 0.071 ± 0.011 mg/g (Figure 3). This yield was higher than that obtained by Liang et al [4] using B. sonorensis for solid-state fermentation. Previous research showed that the main microorganisms producing TMP belong to Bacillus species [4,19].…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Among them, strain LC-6 (B. amyloliquefaciens) had a relatively higher TMP yield of 0.071 ± 0.011 mg/g (Figure 3). This yield was higher than that obtained by Liang et al [4] using B. sonorensis for solid-state fermentation. Previous research showed that the main microorganisms producing TMP belong to Bacillus species [4,19].…”
Section: Discussioncontrasting
confidence: 64%
“…This yield was higher than that obtained by Liang et al [4] using B. sonorensis for solid-state fermentation. Previous research showed that the main microorganisms producing TMP belong to Bacillus species [4,19]. Overall, it is reasonable to select a high-yield TMP-producing Bacillus strain as the initial strain in this study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations